2017
DOI: 10.2319/072317-490.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of soft tissue changes in anterior open bite adults treated with zygomatic miniplate-anchored maxillary posterior intrusion

Abstract: Soft tissue changes following maxillary posterior teeth intrusion with zygomatic miniplates and premolar extractions appear to be stable 4 years after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Limited long-term data were found in the literature regarding the stability of anterior open bite correction in adults treated with maxillary posterior segment intrusion using zygomatic miniplates. Recently, Marzouk and Kassem 5,17 evaluated 26 anterior open-bite patients, who had maxillary posterior segment intrusion with zygomatic miniplates. They found that the intruded maxillary molars relapsed by 10.2% in the first…”
Section: Resultsmentioning
confidence: 99%
“…Limited long-term data were found in the literature regarding the stability of anterior open bite correction in adults treated with maxillary posterior segment intrusion using zygomatic miniplates. Recently, Marzouk and Kassem 5,17 evaluated 26 anterior open-bite patients, who had maxillary posterior segment intrusion with zygomatic miniplates. They found that the intruded maxillary molars relapsed by 10.2% in the first…”
Section: Resultsmentioning
confidence: 99%
“…The data was derived from the sample previously reported by the authors [ 36 , 37 ]. The subjects recruited were 28 young adults (range = 19–28 years) presenting with 3–8-mm anterior open bite and posterior vertical maxillary dentoalveolar excess as determined by initial cephalograms.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported on the findings of skeletally anchored maxillary posterior teeth intrusion [ 19 37 ]. However, few studies [ 30 32 , 37 ] have reported soft tissue changes associated with posterior teeth intrusion (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations